Explaining Stakeholder Identification with Moderate Prestige Collectives: A Study of NASCAR Fans. Issue 9 (September 2019) - Elsbach, Kimberly D.; Cable, Daniel M.
Through two studies of fans who identified with the collective known as NASCAR (the National Association for Stock Car Auto Racing hereafter referred to as Nascar), we examine why stakeholders identify with collectives that are perceived as only moderately prestigious (given that high prestige has been shown, empirically, to be the primary predictor of collective identification because it enhances identifiers' self-esteem). Our findings indicate that identifiers did not perceive Nascar to be high in prestige (compared to other similar collectives) and that their identification was predicted, primarily, by "Perceived Opportunity for Authentic Self-Expression" with Nascar. In addition, across both studies, we found that "patriotism"—a personal value that was difficult for fans to affirm elsewhere—was the most important value that fans perceived they could "self-express" when interacting with Nascar. These findings suggest that individuals may identify with moderate prestige collectives because they provide rare opportunities to express values that are part of their authentic selves, and thus, satisfy these individuals' "needs for authenticity."